The Obesity Epidemic: Analysis of Past and Projected Future Trends in Selected OECD Countries - Sassi, Franco (OECD Publishing, 2009)
This paper provides an overview of past and projected future trends in adult overweight and obesity in OECD countries. Using individual-level data from repeated cross-sectional national surveys, some of the main determinants and pathways underlying the current obesity epidemic are explored, and possible policy levers for tackling the negative health effect of these trends are identified. First, projected future trends show a tendency towards a progressive stabilisation or slight shrinkage of pre-obesity rates, with a projected continued increase in obesity rates. Second, results suggest that diverging forces are at play, which have been pushing overweight and obesity rates into opposite directions. On one hand, the powerful influences of obesogenic environments (aspects of physical, social and economic environments that favour obesity) have been consolidating over the course of the past 20-30 years. On the other hand, the long term influences of changing education and socio-economic conditions have made successive generations increasingly aware of the health risks associated with lifestyle choices, and sometimes more able to handle environmental pressures. Third, the distribution of overweight and obesity in OECD countries consistently shows pronounced disparities by education and socio-economic condition in women (with more educated and higher socio-economic status women displaying substantially lower rates), while mixed patterns are observed in men. Fourth, the findings highlight the spread of overweight and obesity within households, suggesting that health-related behaviours, particularly those concerning diet and physical activity, are likely to play a larger role than genetic factors in determining the convergence of BMI levels within households
Keywords: Social Issues/Migration/Health